Corporate Governance and Competitiveness - The Prospects for Global Convergence - Gandotra, Navdeep Kumar (Prabandhan: Indian Journal of Management, 2010)
The forces of globalization and liberalization have altered the whole market structure and operational behaviour both at the domestic as well as the international level. These waves have resulted in unprecedented changes in the corporate world and have brought an influential impact on the organizational performance. The main outcome is the move towards market economies. The doctrine of liberalization forcefully argues that economic welfare will be improved by freeing private business from regulation by the state. It would stimulate both economic efficiency and growth. Market requires no big administrative apparatus, no central decision making and very little policing other than the provision of a legal system for the enforcement of contracts. Competition has in reality become a discernible force in developing economies. In an increasingly integrated global economy, domestic firms and industries cannot be completely insulated from external competitive pressures. Trade liberalization exposes the business sector to competition from imports, provides access to new technologies and skills from abroad, facilitates the realization of economies of scale in production and stimulates industrial technological activities and competitiveness (Bhalla, 1993 and Wignarja and Taylor, 2003).Global competition is a potent force in ensuring good corporate governance. Corporate governance, which is also the outcome of the new economic policies, has significant impact and contribution towards the stimulation of competitiveness of a firm, industry and nation as a whole. Good corporate governance, complemented by a sound business environment, can strengthen private investment, corporate performance, and economic growth. Corporate governance establishes the relationship among these three groups in determining the direction and performance of the organization (Hunger and Wheelen, 1998).Corporate governance exists at a complex intersection of law, morality, and economic efficiency. The impact of market competition would be greater in firms with efficient governance structure. The substitution effect implies when corporate governance is weak; competition plays an important role as a disciplinary device forcing mangers to improve performance and reduce slack. If competition and corporate governance complements, product market competition might not alone be sufficient to reduce productive inefficiencies in an environment with poor corporate governance. Against this background, the present paper is an endeavour to examine the rationale or relevance of corporate governance in enhancing the organizational competitiveness in the realm of global competition with special reference to developing economies like India.